Hedging your bets : a novel - Denker, Jayne, 1966- (St. Martin's Griffin, 2024)
"Gillian has been happily divorced for several years and, after trying a few dating apps, prefers to stay that way. Navigating her way through dates with fat shamers and lackluster men has left her with no desire to do anything other than work in her garden in her spare time. Who needs rude comments and awkward first-date conversation when soft roses and vibrant tulips are so much better? Noah West has just moved to Willow Cove. After a rough breakup that leaves him looking to get far away, he relocates to the same small town he spent summers in as a teen-and moves right next door to Gillian. A big believer in minimalist design and that the best kind of plants are non-flowering, he knows as soon as he meets his neighbor that they are going to clash on just about everything. Now if only he could keep his eyes off her too. That might be helpful. When a gardening contest brings out the competition in Gillian and Noah, dueling plant arrangements and fiery banter ensues. But is it possible that beneath all their differences, they might just be perfect for each other?"--